Penguatan Fungsi Kelembagaan dan Adopsi Teknologi Tepat Guna pada Wirausaha Tani Kopi di Desa Panduman Kabupaten Jember - Sundari, Sri; Ahmad Ahsin Kusuma Mawardi; Bambang Irawan (SEJAGAT : Jurnal Pengabdian Masyarakat, 2025)
The limited educational background of farmers, low coffee productivity, weak institutional capacity, and inadequate adoption of appropriate technology (AT) are key challenges facing coffee farmer-entrepreneurs in Panduman Village. This community engagement program aimed to strengthen institutional functions and promote the adoption of postharvest AT through a collaborative approach based on the Penta Helix model. The methods included establishing learning centers, conducting technical training, mentoring, on-field demonstrations, and facilitating legal institutional formation and business partnerships. The results demonstrated significant improvements in farmer capacity and institutional function, including the establishment of the Nature School and Farmer Training Center (P4S), improved knowledge and skills, and a shift from traditional to GAP (Good Agricultural Practices) and GMP (Good Manufacturing Practices)-based cultivation and processing. Legalization of farmer groups and formation of inclusive business partnerships in the coffee value chain were achieved, particularly through collaboration with Village-Owned Enterprises (BUMDes). The adoption of AT enhanced the quality and efficiency of postharvest processing. The Penta Helix approach proved effective in transforming rural coffee agribusiness ecosystems towards resilience and sustainability.